Existence results for some interval differential equations (2000)
This paper is concerned with the problem of existence of solutions to interval differential equations which result from attempts to provide a concide interval solution to some differential equations with inexact data or parameters contained in an interval. An extension of the interval iterative scheme of Moore is used to establish the main results which include those of Sveloslav Merkov’s.